Dealing with wind noise on resource constrained acoustic sensors - Alberts, W. C. K.; Lyons, Gregory W. (The Journal of the Acoustical Society of America, 2024)
Single and multiple microphones in small or hand-held devices, i.e., mobile phones, are often single port and without windscreens. In a typical outdoor situation, this configuration can be subject to strong impulsive wind noise events and wind-induced tones. Smart mobile phones can sometimes utilize their significant computational power to employ sophisticated signal processing to reduce or remove wind-associated noise. However, in systems where battery conservation is paramount and computational processing resources are severely limited, alternative strategies must be employed. This presentation will discuss exemplar wind noise data from a single channel, resource-constrained system, methods for wind noise reduction, and results.